Retrospective evaluation of notched and fragmented QRS complex in dogs with naturally occurring myxomatous mitral valve disease - Radu Andrei Baisan (Taylor & Francis Group, 2021)
Myxomatous mitral valve disease (MMVD) is the most common cardiac disease in dogs. The association of QRS notching (nQRS) or fragmentation (fQRS) with disease severity is currently unknown. The study objective was to assess the prevalence of nQRS and fQRS in dogs with MMVD and its severity according to ACVIM classification and to compare the results with a group of healthy dogs. This retrospective cross-sectional study included 34 healthy control dogs and 155 dogs with spontaneous MMVD (42% of dogs in class B1, 23% in class B2 and 35% in class C). fQRS was defined as nQRS complexes in two contiguous leads in the frontal plane (leads I and aVL) and (II, III or aVF). A one-way ANOVA with Bonferroni post-hoc test was used to assess the differences in continuous data between control and MMVD groups. Of the MMVD group, 58% showed nQRS in at least one lead and 27% presented fQRS. There was no difference between the number of leads with a nQRS and disease severity (p = 0.75) nor did the number of leads with a nQRS correlate with left atrial size (r = 0.48; p = 0.5). The number of dogs with fQRS did not differ among classes of MMVD (p = 0.21). nQRS and fQRS were more prevalent in dogs with MMVD compared to control dogs (p < 0.01). This study did not identify any relationship between the number of leads with a nQRS and disease severity. However, dogs with MMVD had a higher prevalence of nQRS and fQRS compared to control group.